2012
DOI: 10.1016/j.clinbiochem.2012.04.004
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Proteomics-based identification of α-enolase as a potential prognostic marker in cholangiocarcinoma

Abstract: Objectives To investigate the association of expression status of α-enolase (ENO1) and clinicopathological outcomes of CCA patients. Design and methods Two-dimensional gel electrophoresis (2-DE) and mass spectrometry (MS) were used to compare differential expressed protein profiles of four human CCA cell lines and H69, a non-malignant biliary cell line, as a control. Immunohistochemical analysis was carried out in tissue-microarray of human CCA tissues (n = 301). Results We identified ENO1 in all CCA cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…For example, ENO1 is involved with various types of human cancer. ENO1 is upregulated in retinoblastoma (4) and is considered a diagnostic marker of hepatocellular carcinoma (5), pancreatic cancer (6), renal cell carcinoma (7,8) and cholangiocarcinoma (9). In addition, abnormally upregulated ENO1 is associated with poor survival and prognosis in patients with mammary carcinoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ENO1 is involved with various types of human cancer. ENO1 is upregulated in retinoblastoma (4) and is considered a diagnostic marker of hepatocellular carcinoma (5), pancreatic cancer (6), renal cell carcinoma (7,8) and cholangiocarcinoma (9). In addition, abnormally upregulated ENO1 is associated with poor survival and prognosis in patients with mammary carcinoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…ENO1 expression is frequently increased in diverse tumors, including head and neck, 6 thyroid, 7 breast, 8 lung, 9,10 prostate, 11 colon and gastric cancer, 12,13 glioma 14 and cholangiocarcinoma. 15 Moreover, overexpression of ENO1 is positively associated with progression and poor prognosis in several tumors.…”
mentioning
confidence: 99%
“…The expression level of this protein was downregulated in H69 cells at all time-points except at 48 h after incubation with O. viverrini ES products, at which point it was significantly upregulated. Interestingly, Yonglitthipagon et al [32] suggested a role for alpha-enolase as a prognostic indicator for CCA patients because the expression level of this protein was upregulated in carcinogenic cells when compared to non-carcinogenic H69 cells. The fact that the expression level of this protein was only upregulated after 48 h could be linked to a change in the cell growth pattern observed for this cell line, but more time-points should be studied to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%